(untitled) (REMUNOM, 2025)
This study investigated the impacts and challenges of family neglect in early childhood education, using a bibliographic methodology. Neglect occurs when there is mistreatment and the omission of basic care, and is a serious social problem. Family neglect is a phenomenon that is often silent and difficult to identify, which makes addressing it even more challenging. For example, children can develop anxiety disorders, learning difficulties and self-esteem problems, and these consequences can last a lifetime. Given this worrying scenario, it is concluded that it is essential to implement a multidisciplinary preventive approach. This involves collaboration between family members, educators and health professionals to identify signs of neglect and provide the necessary support to children at risk. Awareness programs on the importance of adequate care during childhood are essential to promote a healthy and safe environment for children’s development. Only through a joint effort will it be possible to ensure more effective teaching and learning, providing children with the necessary opportunities to grow up healthy and happy.